Study on the Coupled Dynamic Responses of a Submerged Floating Wind Turbine under Different Mooring Conditions - Conghuan Le; Yane Li; Hongyan Ding (Energies, 2019)
A submerged floating offshore wind turbine (SFOWT) is proposed for intermediate water depth (50⁻200 m). An aero-hydro-servo-elastic-mooring coupled dynamic analysis was carried out to investigate the coupled dynamic response of the SFOWT under different mooring conditions subjected to combined turbulent wind and irregular wave environments. The effects of different parameters, namely, the tether length, pretension and the tether failure, on the performance of SFOWT were investigated. It is found that the tether length has significant effects on the motion responses of the surge, heave, pitch and yaw but has little effects on the tower fore-aft displacement and the tether tensions. The increased pretension can result in the increase of the natural frequencies of surge, heave and yaw significantly. The influence of tether failure on the SFOWT performance was investigated by comparing the responses with those of the intact mooring system. The results show that the SFOWT with a broken tether still has a good performance in the operational condition.